ACUTE RENAL FAILURE AFTER CARDIOPULMONARY BYPASS SURGERY IN CHILDREN WITH CONGENITAL HEART DISEASE - E. . Krastyn’Sh; Z. . Staume; Ya. . Auzyn’Sh; Petersons Aigars; A. . Petersons (Вестник хирургии имени И.И. Грекова, 2018)
The article presents the research based on data of 30 children with congenital heart disease. The mean age of the patients was 7 months. It was shown that open cardiac surgery caused an expressed but transitory expression of renal biomarkers, creatinine clearance and serum creatinine level. The frequency of occurrences of acute renal failure was 46,6%. Both biomarkers returned to normal values before discharge from the hospital.